PENYULUHAN BABY MASSAGE TERHADAP TUMBUH KEMBANG BAYI DAN BALITA DI POSYANDU BALITA DUSUN JATIROGO MADIUN - Annida Tri Alawiyah; Kristiyono Putro; Nungki Marlian Yuliadarwati (Jurnal Pengabdian Masyarakat Multidisiplin, 2023)
Counseling was carried out aiming to provide understanding to parents at the Jatirongo Posyandu regarding the importance of giving baby massage to babies. The presentation of the counseling that was carried out included definitions, age and time of implementation, benefits, treatment restrictions and baby massage techniques which could then be carried out again at home. The health promotion media used are in the form of posters and powerpoints accompanied by baby massage techniques. Counseling can be well received and understood and there is a question and answer session related to counseling which is carried out to measure parents' understanding regarding the counseling that has been delivered. Where the results of the final evaluation showed that there was an increase in mother's knowledge regarding the importance of baby massage from 0% to 100%. Counseling activities can increase community knowledge, especially orang tua regarding the importance of baby massage, health education about the benefits and techniques of baby massage can be provided to increase parental knowledge so that parents can do baby massage independently